Severe upper extremity dysfunction after 4CMenB vaccination in a young infant - Tenenbaum, Tobias; Niessen, Johanna; Schroten, Horst (The pediatric infectious disease journal, 2016)
The 4-component meningococcal serogroup B vaccine 4CMenB (Bexsero) is the first vaccine against this serogroup and has been approved by licensing authorities in Europe, Canada and Australia. Therefore, the vaccine may enter soon nationwide vaccine recommendation schemes. We report on a case of a 5-month-old infant who developed prolonged upper extremity dysfunction after the second injection of the 4CMenB vaccine in the left deltoid muscle and was concomitantly applied with 2 routine vaccinations. Myositis, periostitis, (peri-) vasculitis and axillary inflammation were confirmed by magnetic resonance imaging. Two months after initial initiation of an anti-inflammatory and an antibiotic treatment, symptoms completely resolved. Administration of 3 vaccines requires clear recommendations for the preferred injection site in infants because increased reactogenicity of 4CMenB may lead to local severe adverse events.
Gesehen am 19.02.2019